Patient Satisfaction with Public Health Nursing Services - Suprapto, Suprapto; Norma Lalla, Nursyamsi; Arda, Darmi (Window of Health : Jurnal Kesehatan, 2023)
Development efforts in public health are the availability of excellent health services. Public health nurses must have competence, knowledge, skills, and attitudes to realize excellent service. This study aims to determine patient satisfaction with public health nurse services. This type of research uses quantitative research with a cross-sectional study approach, which seeks to analyze variables in accordance with the research objectives, namely patient satisfaction with public health nurse services. The population in this study was all nurses, and it was contained in a structure of 35 people. The sampling technique in this study used the total sampling technique with a sample of 35 respondents. The data analysis method uses bivariate with the chi-square test. The results of the statistical tests showed competence with a p-value of 0.491, work ethics: 0.000, and work discipline 0.046. The conclusion is that patient satisfaction is influenced by ethics and work discipline in providing health services, and patient satisfaction is not influenced by competency certificates. It is recommended that nurses have the ability to implement their skills and knowledge to create excellent health services for patients.